Attitude, Subjective Norms, and Perceived Behavioural Control as Predictors of Entrepreneurial Intentions Among Engineering Students - Mishra, Ankita; Singh, Parwinder (Prabandhan: Indian Journal of Management, 2022)
Entrepreneurship, a significant factor affecting the economy and well-being, is being nurtured by a range of opportunities and programs by the government across several sectors. While these initiatives focus on making physical resources accessible to the aspirants, psychological resources required for successful entrepreneurship have not been focused upon rigorously, especially in India. Entrepreneurial intention has been identified as a significant predictor of entrepreneurial behavior, and understanding its dynamics to promote it is the need of the hour. Entrepreneurship is considered an intentionally planned activity; therefore, the entrepreneurial intention could be explained by the theory of planned behaviour (TPB) factors consisting of attitude, subjective norms, and perceived behavioural control. This study aimed to examine the relationship between TPB components and entrepreneurial intention. The cross-sectional study design was employed to collect the data from 170 students (M = 18.42, SD = 1.02) studying in various engineering colleges in Punjab. The Entrepreneurial Intention Questionnaire (EIQ) developed by LiÃ±Ã¡n and Chen (2009) was used to measure the responses. The data were subjected to mainly correlation and regression analysis. The results indicated a strong association of attitude and perceived behavioural control with entrepreneurial intentions ; whereas, subjective norms reflected a weak association with entrepreneurial intentions. Moreover, perceived behavioural control and attitude towards entrepreneurship were strong predictors of entrepreneurial intentions for this Indian sample. The findings provide educators, administrators, and policymakers valuable insights about the factors to be targeted to strengthen entrepreneurship among budding entrepreneurs.